Bioprospecting and characterisation of heavy metal stress-induced antimicrobials from rhizospheric Bacillus sp. against multidrug-resistant Pseudomonas Aeruginosa (strain ATCC 27853) and Acinetobacter baumannii (strain ATCC-BAA-1605) - Iwarere, Samuel Ayodele (University of Pretoria, 2026)
Dissertation (Meng (Chemical Engineering))--University of Pretoria, 2026.